Centerpiece plate vs. Arch plate fixation in cervical unilateral open-door laminoplasty: a retrospective comparative study - Huo, Lishuang; Liu, Fengyu; Sun, Xianze (Frontiers in Surgery, 2025)
PurposeTo compare the clinical and radiological outcomes of Centerpiece plate and Arch plate fixation in cervical unilateral open-door laminoplasty.MethodsThis study included 102 patients who underwent cervical unilateral open-door laminoplasty with Centerpiece plate fixation (62 patients) or Arch plate fixation (40 patients) between September 2017 and September 2022. Clinical and radiological outcomes were evaluated.ResultsThere were no significant differences in operation time, blood loss, and lamina open angle between the two groups. Before surgery, the two groups had comparable Japanese Orthopedic Association (JOA) scores and Pavlov's ratios. After surgery, the spinal drift distance and Pavlov ratio of the Centerpiece group were smaller than those of the Arch group. Both groups showed significant improvements in JOA scores after surgery and at the last follow-up compared to pre-surgery. At the final follow-up, the Centerpiece group's JOA scores and JOA score improvement rate were lower than those of the Arch group.ConclusionsBoth Centerpiece plate and Arch plate fixation can improve the patient's symptoms. Centerpiece plate fixation has a worse prognosis than Arch plate fixation in cervical unilateral open-door laminoplasty because the ventral prong in the Centerpiece plate may obstruct the spinal cord's backward movement.